2004
DOI: 10.1128/aac.48.8.2951-2957.2004
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid Pharmacokinetics-Pharmacodynamics in an Aerosol Infection Model of Tuberculosis

Abstract: Limited data exist on the pharmacokinetic-pharmacodynamic (PK-PD) parameters of the bactericidal activities of the available antimycobacterial drugs. We report on the PK-PD relationships for isoniazid. Isoniazid exhibited concentration (C)-dependent killing of Mycobacterium tuberculosis H37Rv in vitro, with a maximum reduction of 4 log 10 CFU/ml. In these studies, 50% of the maximum effect was achieved at a C/MIC ratio of 0.5, and the maximum effect did not increase with exposure times of up to 21 days. Conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 18 publications
12
120
1
Order By: Relevance
“…Another study which, though is not specific to INH, also provided the evidence of metabolic activity of cultured macrophage cells (29). On the other hand, Jayaram et al reported that INH remains stable in macrophage cultures (19). Therefore, data of INH metabolism in uninfected macrophage culture are contradictory and further studies are warranted to explore this aspect.…”
Section: Ex Vivo Drug Uptake Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Another study which, though is not specific to INH, also provided the evidence of metabolic activity of cultured macrophage cells (29). On the other hand, Jayaram et al reported that INH remains stable in macrophage cultures (19). Therefore, data of INH metabolism in uninfected macrophage culture are contradictory and further studies are warranted to explore this aspect.…”
Section: Ex Vivo Drug Uptake Studiesmentioning
confidence: 92%
“…The concentration of INH in rat plasma was determined by the method described elsewhere (19), with slight modification. Plasma (50 μl) containing isoniazid was extracted with 100 μl of 10% TCA by vortexing for 30 s. It was then centrifuged (14,000 rpm/10 min).…”
Section: High-performance Liquid Chromatographic Analysis Of Inhmentioning
confidence: 99%
“…PZA is particularly effective against the Mycobacterium tuberculosis in the area of necrosis, where acidic media are available. In vitro studies show that both PZA and INH exhibit a concentration-dependent effect [3,4]. Poor patient outcomes were associated with low levels of INH or PZA [5][6][7].…”
Section: Isoniazidmentioning
confidence: 99%
“…During this time, progress has also been made in the quantitative description of both pharmacokinetics (PK) and in vitro pharmacodynamics (PD) of antituberculosis drugs [17], [18], [19]. Mathematical models that arise from a systems approach offer a unique potential to establish quantitative links across multiple biological scales.…”
Section: Tuberculosis Modellingmentioning
confidence: 99%